Biocontrol of cassava pathogens: A useful approach - Lozano, J.C. (International Center for Tropical Agriculture, 1987)
Research results obtained during 1975-87 on the biocontrol of cassava pathogens are summarized with emphasis on the use of fluorescent pseudomonads as biocontrol agents in different cassava production systems. Evidence of biocontrol of Uromyces spp. by the mycoparasite Darluca filum is reviewed. Findings on biocontrol with the beneficial bacteria Pseudomonas putida and P. fluorescens are examined regarding their isolation, survival, effect on cassava seedlings under greenhouse conditions, and practical applications (bicontrol of Xanthomonas campestris pv. manihotis, Pythium spp., and Diplodia manihotis). Different effects observed with treatments with beneficial bacteria on cassava plant growth are summarized: increased root wt. length, and no., and faster root initiation. These results indicate that the biocontrol of cassava pathogens is feasible. (CIAT)